Effect of Organizational Strategy, in the Context of Change Management and Performance of Companies Listed in Nairobi Securities Exchange in Kenya - Aketch E. Ng’ong’a (Current Aspects in Business, Economics and Finance Vol. 1, 2022)
The study’s goal was to determine the impact of organizational strategy on the performance of Kenyan companies listed on the Nairobi Securities Exchange (NSE). The study’s theoretical foundation encompasses chaos and complexity theory as well as industrial organizational economic theory. The study used a cross sectional survey design on 64 companies listed in the NSE in Kenya with a sample of 38 companies covering five years (2013-2017) as at 30th June, 2017. Purposive sampling was used on four senior managers from listed businesses in the NSE, including Chief Executive Officers, heads of divisions in Human Resource, Finance, and Marketing, for a total sample size of 152 managers. Pre-testing was done on 15 people, and the reliability coefficient(r) was higher than the recommended 0.7. To assess organizational culture and performance, the researchers employed a five-point Likert scale. Primary data came from the semi-structured questionnaire and secondary data came from published sources. According to the research, organizational strategy has a considerable positive impact on the performance of companies listed on the Nairobi Securities Exchange. The study stated that organizations should adopt organizational strategy because it aids in the development of strategic plans, both short and long term, that propel the company to higher performance in a changing business environment. According to the findings, management should design a competitive market strategy that includes long-term objectives and yearly corporate goals that specify important performance metrics for companies listed on the NSE.